2010
DOI: 10.1002/oa.1082
|View full text |Cite
|
Sign up to set email alerts
|

Multiple bone tuberculosis in a child from predynastic Upper Egypt (3200 BC)

Abstract: Tuberculosis, one of the most ancient human diseases, was present in ancient Egypt and has been observed since predynastic times. Excavations in the predynastic to early dynastic necropolis of Adaima, Upper Egypt (3500-2700 BC) led to the discovery of a number of remarkably well-preserved skeletons of children. The skeletal remains of a 4.5-5-year-old child dated from Nagada III A2 (3200-3100 BC) displayed various lesions on the post-cranial skeleton: spondylitis on the thoracic (T12) and lumbar (L1) vertebrae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…This new Neolithic evidence of multifocal, disseminated skeletal TB, with its multiplicity of bony lesions, might be useful for understanding disease progression in the past, and possibly helping scholars in the diagnosis of other skeletons where the evidence is more limited/nonspecific, and remains are incomplete (Wilbur et al, 2009;Roberts et al, 2009) In the bioarchaeological literature, multifocal TB has been reported in a 4-5-year-old child from Predynastic Upper Egypt (AD S 500; 3,200 BC; Dabernat and Crubézy, 2010).…”
Section: Significance For Bioarchaeology and Paleoepidemiology Of Tbmentioning
confidence: 93%
See 2 more Smart Citations
“…This new Neolithic evidence of multifocal, disseminated skeletal TB, with its multiplicity of bony lesions, might be useful for understanding disease progression in the past, and possibly helping scholars in the diagnosis of other skeletons where the evidence is more limited/nonspecific, and remains are incomplete (Wilbur et al, 2009;Roberts et al, 2009) In the bioarchaeological literature, multifocal TB has been reported in a 4-5-year-old child from Predynastic Upper Egypt (AD S 500; 3,200 BC; Dabernat and Crubézy, 2010).…”
Section: Significance For Bioarchaeology and Paleoepidemiology Of Tbmentioning
confidence: 93%
“…Buikstra, 1981;Klaus et al, 2010;Roberts, 2015). In the Neolithic Old World, skeletons with the infection have been reported in the Near East and North Africa (Ortner, 1979(Ortner, , 1999Strouhal, 1987;El-Najjar et al, 1997;Crubézy et al, 1998;Zias, 1998;Dabernat and Crubézy, 2010), with the potential Israeli evidence dating back to the eighth millennium BC (Hershkovitz et al, 2008). Skeletal TB has also been reported from Neolithic continental Europe (Bartels, 1907;Sager et al, 1972;Dastugue and de Lumley, 1976;Bennike, 1999;Gladykowska-Rzeczycka, 1999;Nuorala et al, 2004;Masson et al, 2013Masson et al, , 2015Köhler et al, 2014;Posa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, common areas affected by the disease included the knee [72,73], lytic circumscribed lesions of the cranium [7,74,75], spine [71,76], hip [73,77], elbow [78], and ribs [76]. There is no documentation with regard to dental abnormalities found in juvenile tuberculosis [7,79]. Dental changes briefly mentioned include linear enamel hypoplasia [80,81], carious lesions, and decreased enamel thickness [80].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Dabernat and Crubézy 2010;Lewis 2011;Matos et al 2011;Dawson and Brown 2012, Ioannou et al 2015, Hlavenková et al 2015, Sparacello et al 2017). The reason is that the tuberculosis of bones and joints in children can take on a variety of less evident forms, which complicates the macroscopic evaluation.…”
Section: Introductionmentioning
confidence: 99%